Bad tourists - Carver, Caro, 1978- (Avid Reader Press, 2024)
"Three tight-knit friends embark on an extravagant divorce trip to the Maldives where they can unwind and celebrate a new chapter in midlife -- until they realize the resort of their dreams is harboring a killer"--